Antioxidant activity and cytotoxic effect of frankincense essential oil - Koh, San Aseana (2023)
One of the most rapidly expanding fields of research is the investigation of natural products particularly medicinal plants as a potential source of anticancer drugs. Frankincense essential oil, from the Burseraceae family has been used during religious ceremonies as a ritual incense. The oil is also used to cure wounds, treatment of allergies, snake and bug bites, colds, coughs, diarrhoea, headaches, syphilis, stomach aches and backache. In this study, purchased frankincense essential oil was used and evaluated for its polarity using thin layer chromatography (TLC), detection of classes of secondary metabolites via phytochemical analysis, antioxidant activity using DPPH assay and cytotoxicity on Vero and A549 cell lines via MTT assay. Numerous spots and a broader range of retention factor values were observed in hexane : ethyl acetate (10:3) indicating the presence of polar and non-polar bioactive compounds. The results correlate with the presence of phenols, tannin, coumarin, flavonoids, saponin, alkaloids and glycosides. In DPPH assay, both frankincense essential oil (v/v) and ascorbic acid presented an EC50 value of of 4.73 ± 0.01% and 4.60 ± 0.02 mg/mL, respectively. In MTT assay, the frankincense essential oil did not exhibit cytotoxicity on Vero cells. The essential oil and doxorubicin showed higher cytotoxicity towards the A549 cells with IC50 values of 76.04 ± 0.09 μg/mL and 0.19 ± 0.10 μg/mL for 24- and 72-hours, respectively. This result iii indicates Frankincense essential oil could be a potential antioxidant agent with low toxicity to normal cells. Thus, further investigations should be conducted using pure isolates from the resin to further elucidate its capability as a pharmaceutical drug.